Pseudogymnoascus destructans: Causative Agent of White-Nose Syndrome in Bats Is Inhibited by Safe Volatile Organic Compounds - Sally Padhi; Itamar Dias; Victoria L. Korn; Joan W. Bennett (Journal of Fungi, 2018)
White-nose syndrome (WNS) is caused by Pseudogymnoascus destructans, a psychrophilic fungus that infects hibernating bats and has caused a serious decline in some species. Natural aroma compounds have been used to control growth of fungal food storage pathogens, so we hypothesized that a similar strategy could work for control of P. destructans. The effectiveness of exposure to low concentrations of the vapor phase of four of these compounds was tested on mycelial plugs and conidiospores at temperatures of 5, 10 and 15 °C. Here we report the efficacy of vapor phase mushroom alcohol (1-octen-3-ol) for inhibiting mycelial and conidiospore growth of P. destructans at 0.4 and 0.8 µmol/mL and demonstrate that the R enantiomer of this compound is more effective than the S enantiomer, supporting the finding that biological systems can be sensitive to stereochemistry. Further, we report that vapor phase leaf aldehyde (trans-2-hexenal), a common aroma compound associated with cut grass odors and also the major volatile compound in extra virgin olive oil, is more effective than mushroom alcohol. At 0.05 µmol/mL, trans-2-hexenal is fungicidal to both conidiospores and mycelia of P. destructans.